STUDI FENOMENOLOGI TENTANG MAKNA BERMAIN PADA PERSPEKTIF PRIA PENGGUNA APLIKASI GAMES HAGO “CHAT SUARA” DALAM MENEMUKAN PASANGAN LAWAN JENIS (JODOH) - Ira Hasianna Rambe, Lusi Romaddyniah Sujana (Universitas Riau, 2019)
Technological developments and knowledge facilitate human beings in all respects. One of them is in interacting without having to meet directly. Unconsciously demanding humans understand what is being hit around it and understand what is again the current trend. One of the applications that many people love today is the online games application. New innovation Games apps, unlike in general that only play individual on the app, but rather this app can play with other real individuals, in this application can also play while chatting, so the competition to win More fun. However, this application is widely used as a matchmaking search event or boyfriend call it Hago application. The application that has 5 features one that is widely loved by men and women is